(untitled) (Physical Education, Health and Social Sciences, 2025)
Breast self-examination is a screening method used in an attempt to detect breast cancer. The method involves the woman herself observing and feeling each breast for possible lumps, distortions or swelling. Breast self -examination is recommended because it is safe, easy, feasible, private, painless and require no specific equipment. Breast self- examination plays important role in preventing breast cancer by using standard guidelines. Objectives: Current study was designed to evaluate nurse’s knowledge and practice of BSE in order to decrease breast cancer. The objectives of study were to assess nurse’s knowledge about breast cancer and its relationship to BSE and barriers toward BSE. Method: The descriptive cross- sectional design was used. Study population included 120 nurse’s working in JHL. Nurse’s knowledge was evaluated using a modified questionnaire on Breast cancer prevention awareness. Non- probability sampling technique was used. Results: The response rate was 100%. Females constituted 100% of study participants. 66% nurses were university graduate having Post RN degree. Majority of participants (80%) stated that breast self-examination is a useful tool for early detection of breast cancer but only half of them (47%) were practicing breast self-examination. Majority of the participants had satisfactory level of knowledge but less satisfactory level of practices 50% and 47% respectively. Conclusion: The results of current study revealed nurses’ high level of knowledge but somehow low level of practice about breast self-examination. Therefore, hospital should organize adequate training programs in order to enhance nurses’ practice of breast self-examination according to standard guidelines to prevent or detect breast cancer.